Strength assessment after proximal hamstring rupture: A critical review and analysis. (February 2020) - Fouasson-Chailloux, Alban; Menu, Pierre; Mesland, Olivier; Dauty, Marc
Abstract: Background: Muscular strength should be one of the main parameters to assess the interest or not of surgery after proximal hamstring rupture. Yet, this parameter is difficult to compare between the different studies because of the heterogeneous assessment methods. Methods: We realized a critical review of strength assessment methods used to evaluate treatments performed after proximal hamstring rupture. The studies were selected from several medical databases with the keywords: "proximal hamstring rupture" OR "proximal hamstring avulsion" AND "strength" OR "isokinetic". Findings: 24 articles evaluated muscular strength after proximal hamstring rupture. 7 have been excluded because the method was not described. 6 types of dynamometric evaluation were used: 2 with an isometric method, 3 with a pneumatic isotonic method and 13 with an isokinetic method. Muscular strengths after non-surgical treatment could not be compared because of the low number of studies and different methods of assessment. After surgery, only isokinetic results measured at the angular speed of 60°/s could have been weighted. A 15% strength deficit was shown at >12 months after surgery. Interpretation: Muscular strength assessment methods currently used to evaluate the strength after proximal hamstring rupture are too disparate to clearly define the strength deficit after rupture and surgery. Strength evaluation should be more rigorous in order to prove the real interest of the surgical management. Highlights: After proximal hamstring ruptures, the isokinetic method is the method of reference. The angular speed of 60°/s is the most discriminant one to show a strength deficit. Eccentric evaluation should be generalized to test precisely the muscular strength.